2016
DOI: 10.1111/papt.12101
|View full text |Cite
|
Sign up to set email alerts
|

Attachment style and readiness for psychotherapy among psychiatric outpatients

Abstract: Insecure attachment may influence prospective patients' readiness for psychotherapy. Patients with an avoidant attachment style may need assistance in preparing for the relational aspects of psychotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Our results illustrate the importance of the attachment system for advanced cancer patients' mental health and highlight the challenge of caring for dismissingly attached patients. Several studies in mental health settings have shown that patients with a dismissing attachment style have more difficulties about seeking help (Kealy et al, 2016). Furthermore, psychotherapy is less effective in these patients (Wiseman & Tishby, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Our results illustrate the importance of the attachment system for advanced cancer patients' mental health and highlight the challenge of caring for dismissingly attached patients. Several studies in mental health settings have shown that patients with a dismissing attachment style have more difficulties about seeking help (Kealy et al, 2016). Furthermore, psychotherapy is less effective in these patients (Wiseman & Tishby, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that cognitive behavioral therapy as an adjunction to conventional dermatologic treatments may be particularly beneficial for patients with more severe pre-treatment psychopathology in improving psoriasis severity, anxiety, and depression symptoms (Sijeric et al, 2019). Although both avoidant attachment (Kealy et al, 2017) and alexithymia (Ogrodniczuk et al, 2011) are negatively associated with openness to personal disclosure in the therapy relationship, patients with these dysfunctional personality traits could benefit from personalized psychological interventions that focus on their negative body image and make them more resilient to social stigma.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…8,9 With regard to motivation for therapy, attachment anxiety showed a positive association with treatment seeking, while attachment avoidance was negatively associated with willingness for personal disclosure. 10 Previous studies have examined the moderating effects of attachment patterns on therapeutic outcomes. 11 An overview of attachment and psychotherapy was recently published by Slade and Holmes.…”
Section: Introductionmentioning
confidence: 99%